GOVERNANCE AND MACROECONOMIC DETERMINANTS OF OIL IMPORT DEPENDENCY: A SUSTAINABILITY PERSPECTIVE FROM INDONESIA - Ismail Kadir H. Palladjarang (Journal of Social and Economics Research, 2025)
This paper assesses how macroeconomic conditions shape Indonesia’s oil and gas (O&G) import dependency over 2000–2024. Using an explanatory, single-country, annual time-series design, we estimate a linear log-level model via Maximum Likelihood, relating oil and gas import value to real GDP growth, the rupiah time-deposit interest rate, and CPI inflation. To retain parsimony, the baseline omits controls, results are interpreted as conditional associations. Findings show growth is positive and significant (β=0.052, p=0.003), the deposit rate is negative and significant (β=−0.050, p<0.001), while inflation is small and not significant (β=−0.004, p=0.608), model fit is R²=0.620. Semi-elasticities imply that a 1-pp increase in growth is associated with ≈5.2% higher import values, whereas a 1-pp rise in the deposit rate is associated with ≈5.0% lower values. These results indicate an income channel under short-run supply inelasticity and a dominant aggregate-demand/financing-cost channel that outweighs appreciation-induced cheap-import effects. Policy implications for a blue–green economy include coordinated monetary–trade–energy governance, disciplined procurement and hedging, and structural measures energy efficiency, transport electrification, and fuel-mix diversification so expansions do not mechanically raise fossil import dependence. Limitations include the absence of key controls (exchange rate, oil prices, domestic production).